Intracellular Eimeria bovis macromeront formation induces bystander cell accumulation and TNT formation - Fischer, Jobst; Sous, Lara; Velásquez, Zahady D.; Hermosilla, Carlos; Taubert, Anja (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEimeria bovis first merogony is an intracellular process ( 3 weeks) resulting in the formation of large macromeronts (≤ 400 μm) containing up to 140,000 merozoites I, each. The production of merozoites I poses critical metabolic stress on bovine endothelial host cells, leading to mitochondrial dysregulation and premature senescence. In this context, an accumulation of non-infected bystander cells (BCs) around E. bovis macromeront-carrying host cells (MCHCs), eventually supporting MCHCs, was observed.MethodsBC accumulation was quantified by 3D confocal microscopy. A meront-transfer-system was established to evaluate the supportive BC capacity of different cell types. Since healthy cells might support stressed cells by transferring cargo like mitochondria via TNTs, we studied if E. bovis infection affected cellular TNT formation. By utilizing the meront-transfer-system, recipient non-infected BCs were pre-treated with inhibitor of TNT formation (cytochalasin B) and the effect on E. bovis development was estimated in BC-MCHC-cocultures. To study the transfer of mitochondria via TNTs, non-infected and E. bovis-infected cells where stained with respective dyes and cargo transfer was illustrated.ResultsIn E. bovis-infected cell layers, an increase of BCs at all sides of MCHCs was stated, thereby correlating with meront sizes and maturation. When using different cell types as BCs, we showed that macromeront development was best supported by human endothelial cells, followed by human fibroblasts and bovine endothelial cells. Overall, TNT numbers were increased in E. bovis-infected cell layers. The relevance of TNTs for parasite development was underlined by selective BC cytochalasin B treatments, which blocked both TNT formation and merozoite I production. Given that TNT-based transfer may improve the energetic status of E. bovis-infected cells, we observed bidirectional mitochondrial transfer between non-infected and E. bovis-infected cells, thereby potentially helping to restore the energetic status of the infected host cell.DiscussionBystander cell-based TNT-mediated mitochondria transfer may evidence a new mechanism of parasite-induced host cell modulation, aiding MCHCs to support parasite proliferation.